Modification effects of Na-bentonite catalyst with organic compounds increasing hydrogen production from biomass pyrolysis - Dwi Irawan; Widya Wijayanti; Slamet Wahyudi; I.N.G. Wardana (Case Studies in Chemical and Environmental Engineering)
Organic compounds containing –OH and CO groups can enhance the catalytic effectiveness of Na-bentonite. This catalyst was employed to break radical compounds generated during the slow pyrolysis of corn cob powder biomass, which was heated to a temperature of 550 °C in a fixed-bed reactor. The results indicated that using organic compound-modified Na-bentonite catalysts could increase hydrogen production by up to 23.4 %. The presence of organic compounds with antioxidants and aromatic rings serves as electron donors, facilitating the reforming of volatile compounds to produce hydrogen-rich gas. This study demonstrates the potential of low-cost and eco-friendly catalysts for hydrogen production through biomass pyrolysis.